2000
DOI: 10.1093/emboj/19.9.2034
|View full text |Cite
|
Sign up to set email alerts
|

TCRalpha enhancer activation occurs via a conformational change of a pre-assembled nucleo-protein complex

Abstract: The TCR a enhancer (Ea) has served as a paradigm for studying how enhancers organize trans-activators into nucleo-protein complexes thought to recruit and synergistically stimulate the transcriptional machinery. Little is known, however, of either the extent or dynamics of Ea occupancy by nuclear factors during T cell development. Using dimethyl sulfate (DMS) in vivo footprinting, we demonstrate extensive Ea occupancy, encompassing both previously identi®ed and novel sites, not only in T cells representing a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 57 publications
7
41
0
Order By: Relevance
“…Specifically, we probed Vβ cross-linking to HindIII fragments containing either of its two substrates (Dβ1 or Dβ2), or the transcriptional enhancer Eβ, which generates active chromatin over the DβJβ clusters (10,31). Regardless of the vantage point, nearly all Vβ gene segments interact more frequently with the DβJβ recombination center in DN thymocytes compared with CD19 + pro-B cells purified from RAG-deficient bone marrow ( Fig.…”
Section: Spatial Access Of Vβ Gene Segments To the Dβjβ Recombinationmentioning
confidence: 99%
“…Specifically, we probed Vβ cross-linking to HindIII fragments containing either of its two substrates (Dβ1 or Dβ2), or the transcriptional enhancer Eβ, which generates active chromatin over the DβJβ clusters (10,31). Regardless of the vantage point, nearly all Vβ gene segments interact more frequently with the DβJβ recombination center in DN thymocytes compared with CD19 + pro-B cells purified from RAG-deficient bone marrow ( Fig.…”
Section: Spatial Access Of Vβ Gene Segments To the Dβjβ Recombinationmentioning
confidence: 99%
“…The 116-bp Tα1-Tα2 fragment constitutes the core enhancer with essential binding sites for the constitutive TFs CREB/ ATF, TCF-1/LEF-1, Runx1, and Ets-1 that bind cooperatively in an allor-none fashion [36,[56][57][58]. These TFs are bound to a primed Eα prior to its activation in DN3a thymocytes as well as when the enhancer is fully active in eDP and lDP thymocytes [14,46,59]. Although the Tα1-Tα2 fragment is efficient in activating transcription and gene segment recombination at short distances in the context of a transgenic recombination reporter construct, is not sufficient to activate endogenous Tcra VJ recombination at large distances [36,60].…”
Section: Regulatory Cis-elements Present At the Tcra/tcrd Locusmentioning
confidence: 99%
“…Recent experiments using chromatin immunoprecipitation to compare the active and inactive Eα enhanceosomes assembled in DP thymocytes and αβ T lymphocytes, respectively, have revealed that the [14,[57][58][59]62,76]. The TFs are represented by colored ovals and their identity is indicated.…”
Section: Eα and Eδ In Mature αβ And γδ T Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…23 During these early thymocyte stages, Ea is not functionally active but is primed through the assembly of multiple constitutive TFs that bind cooperatively to enhancer DNA and the presence of the H3K4me1 histone mark. [31][32][33][34][35] During b-selection, Ea is activated and Ed is inactivated during the transition from DN3a to DP thymocytes. 32 Pre-TCR signaling triggers the formation of a chromatin hub through physical interactions among TFs bound to the Ea enhanceosome and Ca-proximal Va-and Ca-distal Ja promoters in a genomic region of approximately 500 kb.…”
Section: 19mentioning
confidence: 99%